5,7-Dihydroxy-4-Methylcoumarin as a Functional Compound for Skin Pigmentation and Human Skin Safety - Ye-Jin Lee; Yang Xu; Chang-Gu Hyun (Pharmaceuticals)
Background/Objectives: This study aims to investigate the effects of 5,7-dihydroxy-4-methylcoumarin (5,7D-4MC) on melanogenesis in B16F10 murine melanoma cells and to evaluate its safety as a potential ingredient for functional cosmetics and therapeutic agents targeting pigmentation-related disorders. Method: The cytotoxicity of 5,7D-4MC was assessed using an MTT assay, and melanin content and tyrosinase activity were measured at different concentrations (25, 50, 100 µM). Western blot analyses were conducted to evaluate the expression of key melanogenesis-related proteins (TYR, TRP-1, TRP-2, and MITF) and to investigate the regulation of major signaling pathways, including PKA/cAMP, GSK3β, and PI3K/AKT. Additionally, a human primary skin irritation test was performed on 32 participants to assess the dermatological safety of 5,7D-4MC. Results: 5,7D-4MC did not affect cell viability at concentrations below 100 µM and significantly promoted melanin production in a dose-dependent manner. Tyrosinase activity and the expression levels of melanogenic proteins increased significantly following 5,7D-4MC treatment. PKA and GSK3β pathways were activated, while the PI3K/AKT pathway was downregulated. The skin irritation test showed that 5,7D-4MC exhibited low irritation potential at concentrations of 50 µM and 100 µM. Conclusions: 5,7D-4MC enhances melanogenesis and demonstrates low skin irritation, making it a promising candidate for therapeutic applications in treating hypopigmentation disorders, such as vitiligo, as well as a functional cosmetic ingredient. However, further studies involving human melanocytes and clinical trials are required to validate their efficacy.